Perinatal outcomes and factors affecting the survival rate of fetuses with twin-to-twin transfusion syndrome treated with fetoscopic laser coagulation: a single-center seven-year experience. (12th December 2022) - Kim, Rina; Lee, Mi-Young; Won, Hye-Sung; Kim, Jung-Min; Lee, Yoo-Jin; Jeong, Ba-Da; Kim, Hwa-Jung
Abstract: Objectives: This single-center study aimed to assess the perinatal outcomes and its associated factors in fetuses with twin-to-twin transfusion syndrome (TTTS) treated by fetoscopic laser coagulation (FLC). Methods: In this retrospective study, we included fetuses prenatally diagnosed with TTTS at Asan Medical Center, Seoul, Korea, between October 2011 and December 2018. All patients with TTTS stage II or higher and those with stage I TTTS coupled with symptomatic polyhydramnios or cardiac dysfunction were eligible for FLC. Results: A total of 172 cases of monochorionic diamniotic twins and one case of dichorionic triamniotic triplets were prenatally diagnosed with TTTS and treated with FLC. The median gestational ages (GAs) at diagnosis and FLC were 20.3 and 20.5 weeks, respectively. The median GA of survivors at delivery was 32.5 weeks. The overall at least one twin- and double-survival rates within 28 days after birth were 82.1% and 55.5%, respectively. The GAs at diagnosis and FLC, Quintero stage, inter-twin weight discordance, associated selective intrauterine growth restriction (sIUGR), procedure time, volume of amnioreduction, preterm prelabor rupture of membranes (PPROM) within one week after FLC, intraoperative intrauterine bleeding, and chorioamnionitis were significant predictive factors of perinatal death. Associated sIUGR, absent end-diastolic flow of umbilical artery, and abnormal cord insertion were significantly associated with donor demise in utero, whereas lower GA at diagnosis and FLC, smaller twins at FLC, pulsatile umbilical vein, and presence of mitral regurgitation were significantly associated with recipient demise in utero . Since the application of the Solomon technique, the survival rate has improved from 75.4% to 88.8%. The FLC before 17 weeks was associated with PPROM within one week after FLC and lower survival rate, whereas that after 24 weeks was associated with twin anemia-polycythemia sequence and higher survival rate. We reached a survival rate of 82% for at least one survival with only 12 procedures. Conclusions: FLC is an effective treatment for TTTS. The learning curve reached the acceptable target faster than in previous studies. Several prenatal parameters are identified as predictive factors of fetal survival in TTTS treated with FLC.